Cooperation Between Stakeholders to Ensure the Roma Child’s Right to Education: An Analysis of Teachers’ Experiences - Gudžinskienė, Vida; Kairienė, Brigita; Raudeliūnaitė, Rita; Petrauskienė, Alina; Sadauskas, Justinas; Žibėnienė, Gintautė (Pedagogika, 2025)
The aim of the article is to draw on the experiences of teachers working with Roma children to shed light on the role of cooperation in guaranteeing the right to education for Roma children. Data was collected through semi-structured interviews. Qualitative content analysis was performed in accordance with the inductive logic of categorization based on the research data. The findings revealed positive and negative aspects of parents’ cooperation with the school in ensuring Roma children’s right to education.